Tourism in Odisha: An Engine of Long Run Growth - Mishra, P K; Rout, Himanshu B; Sanghamitra (Journal of Tourism Management Research, 2016)
In this globalized era, travel and tourism has become an indispensable economic activity world over. It has the potential to strengthen the socio-economic foundation of a nation. It has the capability to disseminate the peace message across the globe. It is well-known for job creation, foreign exchange earnings, revenue and income generations, and developing socio-economic infrastructures. Thus, it is critical for unemployment reduction, poverty alleviation, inequality reduction, and bringing up balanced regional development. It is instrumental for achieving inclusive and sustainable growth of a nation like India and her States. It is with this backdrop, this paper is an attempt to assess the role of tourism in Odisha, an eastern State of India, as an engine of long-run economic growth. In recent years, tourism has grown considerably due to the availability of good infrastructure facilities, favorable government policies, improvement of existing tourist locations, development of new tourist destinations and strong growth of hotel and restaurant industry in the State. This is reflected in the growing number of both domestic and foreign tourists to the State. In a multivariate framework, the use of multiple regression model over the period spanning from 1990-91 to 2011-12 provides the evidence of the positive contribution of the tourism sector to the economic growth of Odisha thereby justifying the role of tourism as an engine of long term growth of the State. Hence, the government of Odisha should formulate plans and policies such that tourism activities are promoted to lead a stable and sustainable growth of the State.